Teaching English and Stress: Teacher Trainees vs. Experienced Teachers - Latiff Azmi, Mohd Nazri (2012)
The study was conducted during a teaching practicum undergone by a group of Diploma of TESL students of Universiti Sultan Zainal Abidin, Terengganu. The purposes of doing this study were to investigate the element of stress faced by both the English language teacher trainees (Diploma TESL students) and also the experienced English teachers (trainee’s school advisors) and also to know the relevant factors of the problem. There were 51 English teacher trainees and 38 experienced English teachers participated in answering an established and adapted set of questionnaires and a few of them also involved in a semi-structured-interview. The findings show that the experienced teachers have suffered from a stressful life being English teachers due to several reasons and at the same time the teacher trainees have a tendency of having the same problem.